Servant leadership style，team psychological safety, team potency and environmental uncertainty on Team innovation performance: An analysis of high-tech enterprise employees of China - Nana Liu; Siti rohaida mohamed zainal (Environment and Social Psychology, 2025)
This study investigates the influence of servant leadership style, team psychological safety, team potency, and environmental uncertainty on team innovation performance among employees in China’s high-tech enterprises. Drawing on Path-Goal Theory and High-Level Echelon Theory perspectives, the research aims to understand how leadership behaviors and contextual factors jointly shape team innovation outcomes. A total of 325 questionnaires were collected from high-tech enterprise teams across Shandong province in China using a structured questionnaire, and analyzed using structural equation modeling (SEM) with SmartPLS 4.1.1. The results reveal that servant leadership and team psychological safety positively affects team innovation performance through enhanced team team potency. Furthermore, environmental uncertainty moderates the relationship between team potency and innovation performance, indicating that high uncertainty amplifies the positive effects of potent teams. These findings provide both theoretical and practical implications: theoretically, they extend leadership and innovation research by integrating servant leadership and contextual contingencies; practically, they offer guidance for managers in fostering safe, empowered, and resilient teams capable of innovation under uncertain market conditions.